The Use of an Atmospheric Model to Simulate the Rocket Exhaust Effluents Transport and Dispersion for the Centro de Lançamento de Alcântara - Schuch,Daniel (2017)
ABSTRACT: This paper introduces a new approach to represent the rocket exhaust effluents into an atmospheric dispersion model considering the trajectory and variable burning rates of a Satellite Vehicle Launcher, taking into account the buoyancy of the exhausted gases. It presents a simulation for a Satellite Vehicle Launcher flight at 12:00Z in a typical day of the dry season (Sept 17, 2008) at the Centro de Lançamento de Alcântara using the Weather Research and Forecasting Model coupled with a modified chemistry module to take into account the gases HCl, CO, CO2, and particulate matter emitted from the rocket engine. The results show that the HCl levels are dangerous in the first hour after the launching into the Launch Preparation Area and at the Technical Meteorological Center region; the CO levels are critical for the first 10 min after the launching, representing a high risk for human activities at the proximities of the launching pad.